Service-learning: mengungkap definisi untuk pembelajaran abad ke 21 - Maznah Ibrahim,; Norain Azlan,; Nor Afian Yusof,; Jamsari Alias,; Najah Nadiah Amran, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Service-Learning or the learning based on service is defined as a method of teaching and learning strategy which optimized experiences in serving the community. Although this practice of teaching and learning has given positive impacts; practitioners and researchers alike are still uneven in their consent regarding the best way to define and characterize the concept of Service-Learning. The main focus of this article is to analyze the key elements in the definition about Service Learning. This article will discuss and elaborate on the concept of Service Learning into four main parts, namely; a general explanation of Service-Learning, different kinds of participation in Service-Learning, the approaches in Service-Learning and the impacts of Service-Learning. In confronting the challenges of the 21st century learning strategy, the implementation of Service- Learning as a learning process based on experiences is timely because it provides students with a strong knowledge for the content of the course, the skills required by the market career, also in instilling positive values required for community development and community change.